Hogar : la memoria intangible de la casa (2017)
I approached to my final Design project exploring a living conflict I perceive from my second discipline, Architecture: what it's projected and what it's built, sometimes, could not be aligned with how the final user lives. In order to understand this tension, I researched the concepts of house and home, as a parallel to the material and immaterial aspects related to the conflict. The house is understood as the tangible and physic part of our daily life, the one in which living is materialized. The home is seen as the personal and individual experience of living, which is built in our memory and is carried by us along our lives. From the theoretical construction of these concepts, the project is a personal exploration looking forward to my professional practice as designer. Integrating the architectonic and design languages, the project is developed around the creation of an experience in order to share and communicate the result of the research process.